A Surgical Approach to Treat Painful Neuromas of the Supraorbital and Supratrochlear Nerves with Implantation of the Proximal Stump into the Orbit. Issue 4 (December 2019) - Hanwright, Philip; Yang, Robin; Chopra, Karan; Dorafshar, Amir; Dellon, A. Lee; Williams, Eric
Frontal neuralgia causally related to trauma to the supraorbital and supratrochlear nerves remains a difficult problem to resolve. A peripheral nerve approach to this problem would involve neuroma resection and relocation of the proximal nerve stump to a location away from the vulnerable supraorbital ridge. A retrospective chart review was done to identify patients with frontal pain related to supraorbital trauma who underwent operative interventions to solve this problem by neuroma resection and relocation of the proximal stumps into the orbit. Eight patients were identified for inclusion in this study. At a mean of 16 months after surgery, there was a significant change in the visual analog score from a mean of 9.4 to 2.8 ( p < 0.05), with 88% of the patients reporting a >50% reduction in pain postoperatively. There was one treatment failure. There were no postoperative complications. The strategy of relocating the proximal end of the supraorbital and supratrochlear nerves into the posterior orbit after resecting the painful neuromas can successfully manage posttraumatic craniofacial pain related to these injured nerves.